Productora y comercializadora de Dulces típicos en Colombia (2021)
This document is evidenced as a business plan report, it reflects the creation of a company that produces and markets typical and traditional Colombian sweets, which intends to put into practice the knowledge acquired throughout the professional career. Using the tools acquired throughout the professional career to develop a series of analyzes that lead to an organized, profitable and efficient and effective business plan; In this way examine the creation of an innovative company, which provides healthy and healthy products to consumers and at the same time satisfies the taste needs of each individual. The business opportunity is concise starting because in Colombia there is no similar or equal place where the main problem of this project can be solved, which is to make the most of those fruit crops that are not used as a whole. to seek to renew in the final consumers their identity and traditional culinary roots.